Second-hand smoke and chronic bronchitis in Taiwanese women: a health-care based study - Lee Chung-Ying; Huang Chia-Tsuan; Hwang Jhi-Jhu; Lee Chien-Hung; Wu Kuen-Yuh; Chong Inn-Wen; Feng Nan-Hsiung; Wu Chia-Fang; Chou Shao-Ting; Christiani David C; Wu Ming-Tsang (BMC, 2010)
Abstract Background Cigarette smoking cannot fully explain the epidemiologic characteristics of chronic obstructive pulmonary disease (COPD) in women, particularly for those who rarely smoke, but COPD risk is not less than men. The aim of our study is to investigate the relationship between second-hand smoke (SHS) exposure and chronic bronchitis in Taiwanese women. Methods We used Taiwan's National Health Insurance Bureau claims data in 1999, and cross-checked using criteria set by the American Thoracic Society; there were 33 women with chronic bronchitis, 182 with probable chronic bronchitis, and 205 with no chronic bronchitis during our interview time between 2000 and 2005. We measured second-hand smoke (SHS) exposure by self-reported measures (household users and duration of exposure), and validated this by measuring urinary cotinine levels of a subset subjects. Classification of chronic bronchitis was also based on spirometry defined according to the GOLD guidelines to get the severity of COPD. Results Women who smoked and women who had been exposed to a lifetime of SHS were 24.81-fold (95% CI: 5.78-106.38) and 3.65-fold (95% CI: 1.19-11.26) more likely to have chronic bronchitis, respectively, than those who had not been exposed to SHS. In addition, there was a significant increasing trend between the severity of COPD and exposure years of SHS (p < 0.01). The population attributable risk percentages of chronic bronchitis for smokers and those exposed to SHS were 23.2 and 47.3% respectively. Conclusions These findings indicate that, besides cigarette smoking, exposure to SHS is a major risk factor for chronic bronchitis in Taiwanese women.